Website MTs Yapima Depok - Ahmad Mugi Raharjo; Muhammad Yunus Rangkuti; Fathur Nurrohman; Satria Giovan (shofanah Media Berkah, 2026)
The MTs Yapima Depok website is an official information platform designed to provide comprehensive and accurate information about educational services and activities at Madrasah Tsanawiyah Yapima Depok. This website serves as a communication and publication medium that presents the school profile, vision and mission, organizational structure, academic programs, student activities, and new student admission information. In addition, the website supports transparency and public access to information for students, parents, teachers, and the wider community. Through an informative and user-friendly interface, the MTs Yapima Depok website is expected to enhance information services, strengthen the institution’s image, and support the integration of information technology in madrasah education management.